Transformation of Human Resource Functions and Islamic Work Ethics in Islamic Financial Institutions in Indonesia (Literature Study) - Yudi Siswadi; Andri Soemitra; Zuhrinal.M. Nawawi (International Journal Of Economics Social And Technology, 2023)
Shift role source Power man based on a change in management paradigm Source Power human. Along time, HR management has experience shift in paradigm. HR Management so far This has through three phase changes: first. Department of Personnel in the 1970s-1980s, second. Human Resource Strategic, 1980s-1990s, and thirdly, Saat This Talent management (management talent). Changes in the function of human resources are no longer carrying out traditional activities such as staffing, compensation, or recruitment, but rather the final results. Inside change The business environment includes internal and external aspects. Internal changes look at various factor in influencing organizations’s change resource human, such as: top management, organizational structure, organizational culture, organizational size. Temporary change external look at various factor outside organization like characteristics force employment, demographics and trends economics and organization, which then influence change role resource man as well as ethos Work particularly in Islamic financial institutions. Study This use literature study with the method study qualitative with content analysis from articles obtained in the Google Scholar database and interviews using technique focus group discussion (FGD). Research results This show that aspect Culture Organizational and Managerial / Leadership, aspects HR competence and aspects HR behavior has connection in HR Practices and Islamic Work Ethics in Islamic Financial Institutions